2013
DOI: 10.1021/ja403001q
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Human Prion Protein Fragment Reveals a Motif for Oligomer Formation

Abstract: The structural transition of the prion protein from α-helical to β-sheet rich underlies its conversion into infectious and disease-associated isoforms. Here we describe the crystal structure of a fragment from human prion protein consisting of the disulfide bond linked portions of helices 2 and 3. Instead of forming a pair-of-sheets steric zipper structure characteristic of amyloid fibers, this fragment crystallized into an β-sheet rich assembly of hexameric oligomers. This study reveals a never before observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(86 citation statements)
references
References 29 publications
4
82
0
Order By: Relevance
“…Association interface in the oligomers was shown to be mediated by the interactions between the D-strands of adjacent b-2m molecules based on structural and kinetic studies [88,89]. Significant amounts of b-structure have been detected in oligomers of prion protein (PrP) [90,91]. PrP oligomers formed at low pH were b-sheet rich and had lower stability and lower extent of b-structure compared to fibrils [90,92,93].…”
Section: Other Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Association interface in the oligomers was shown to be mediated by the interactions between the D-strands of adjacent b-2m molecules based on structural and kinetic studies [88,89]. Significant amounts of b-structure have been detected in oligomers of prion protein (PrP) [90,91]. PrP oligomers formed at low pH were b-sheet rich and had lower stability and lower extent of b-structure compared to fibrils [90,92,93].…”
Section: Other Proteinsmentioning
confidence: 99%
“…Thermal unfolding of PrP resulted in the formation of a different type of PrP oligomers, where parts of C-terminal domain (residues 148-175) were unfolded and then refolded to b-structure [94,95]. Crystal structure of oligomers of a PrP-derived peptide [91] showed that this peptide (residues 177-182 and 211-216 of PrP covalently linked via a disulfide bond) was assembled into b-sheet-rich hexamers. The overall structural organization of this hexamer was rather unique, with three four-stranded, anti-parallel b-sheets being arranged like the faces of a triangular prism (Fig.…”
Section: Other Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the short peptide, however, FTIR spectroscopy could not determine the conformational changes in detail because the peptide has several conformations and a flexible structure in solution [9]. X-ray crystallography and nuclear magnetic resonance (NMR) are usually employed to determine the structure of peptides [15]- [17], but while these analytical methods are excellent for three-dimensional structural determination at the atomic level, they are also time consuming, and once analyzed, samples cannot be re-used for other analytical methods. In contrast, IR absorption spectral measurements are comparatively simple, and the spectra are sensitive to the secondary structures of the peptides [18].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1, the mathematical formula for B Chain got from A Chain is [1,4] 2 human 4UBY Class 8 [1,4] 3 human 4UBZ Class 8 [1,4] 4 PrP(126-132) human 4W5L Class 8 [1,4] 5 human 4W5M Class 8 [1,4] 6 human 4W5P Class 8 [1,4] 7 PrP(127-133) human 4W5Y Class 6 [1,4] 8 human 4W67 Class 6 [1,4] 9 human 4W71 Class 6 [1,4] 10 PrP(127-132) human 4WBU Class 8 [1,4] 11 human 4WBV Class 8 [1,4] 12 human 3MD4 antiparallel (P 2 1 2 1 2 1 ) 13 human 3MD5 parallel (P 1 2 1 1) 14 human-M129 3NHC Class 8 [1] 15 human-V129 3NHD Class 8 [1] 16 PrP(137-142) mouse 3NVG Class 1 [1] 17 PrP(137-143) mouse 3NVH Class 1 [1] 18 PrP(138-143) Syrian hamster 3NVE Class 6 [1] 19 human 3NVF Class 1 [1] 20 PrP(142-166) sheep 1G04 β-hairpin [3] 21 PrP(170-175) human 2OL9 Class 2 [1] 22 elk 3FVA Class 1 [1] 23 PrP(177-182, 211-216) human 4E1I β-prism I fold [2] (P 2 1 2 1 2 1 ) 24 human 4E1H β-prism I fold [2] (P 2 1 2 1 2 1 ) …”
mentioning
confidence: 99%